ANALISIS KINERJA PEGAWAI SUB. BIDANG KEBERSIHAN DINAS CIPTA KARYA DAN TATA RUANG DALAM PENATAAN KUALITAS KEBERSIHAN DI KABUPATEN CIREBON - Andri Tria Hermawan; Moh Sutarjo; Sri Wulandari (Jurnal Ilmiah Publika, 2016)
ABSTRACT Research entitled "Employee Performance Analysis Sub. Cleaning Department of Cipta Karya and Spatial Planning of Cirebon Regency in the Arrangement of Cleanliness Quality in Cirebon Regency. The problem is motivated by the lack of optimal work from the bureaucracy in the quality management of cleanliness in Cirebon Regency, the problem is allegedly arising due to the lack of optimal performance of employees in improving the quality of cleanliness in Cirebon District, seen in the things that are the work of Sub. The area of cleanliness of the Cipta Karya and Spatial Planning Office of Cirebon Regency is not as expected, namely the clean, comfortable and beautiful environment, as well as the work behavior and personal nature of employees who are less disciplined, lazy and careless in working so that the results are not as expected. Therefore this study is directed to determine the performance of employees in improving the quality of cleanliness in Cirebon Regency.            The method used in this study is a qualitative method through a descriptive approach and the data presented are the results of an assessment and interview with the community as users who feel the quality of cleanliness in Cirebon District (Sumber City) with Sub employees. The cleanliness of the Cipta Karya and Spatial Planning Office in Cirebon Regency, while the key informant in this study was the Head of the Hygiene Section. Data sources used in this study are primary data and secondary data. Primary data obtained in this study from the results of observations and interviews, while secondary data is obtained by looking for data from the literature to support the data that has been obtained.Based on the research conducted, it was obtained the results, that the performance of employees in structuring the quality of cleanliness in Sub. The cleanliness of the Cipta Karya and Spatial Planning Office in Cirebon Regency has not been optimal, seen from the 3 (three) dimensions of work, namely (1) Work results are not optimal seen from the results of work less than expected, namely a clean environment; (2) Work behavior is not optimal seen from employees who are not disciplined and lazy in working; (3) The personal nature that has to do with work is not yet optimal seen from the lack of enthusiasm of employees and carelessness in work. In essence, all employee performance will produce maximum results if in all of the achievement of these goals are maximized. Like in Sub. The area of cleanliness of the Cipta Karya and Spatial Planning Office of Cirebon Regency the performance of employees in cleaning the quality of cleanliness in Cirebon District (the source city) has been good in planning the administration but in achieving that the performance of employees has not been maximally created so that the quality of cleanliness is not yet maximal.